1996
DOI: 10.2307/3432916
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Liver Diseases Induced in Flounder (Platichthys flesus) after Long-Term Exposure to Contaminated Sediments in Large-Scale Mesocosms

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Several comprehensive studies using histopathological parameters have demonstrated clear relationships between environmental pollution and fish disease. The relationships, for instance, between pollution levels, biomarker responses and skin and liver diseases in flounder after long-term exposure to PAH-and PCB-contaminated sediments in a mesocosm study were reported by Vethaak et al (1996). Existing long-term data on external visible diseases for flounder from the southern Baltic could provide links to population health.…”
Section: Discussionmentioning
confidence: 86%
“…Several comprehensive studies using histopathological parameters have demonstrated clear relationships between environmental pollution and fish disease. The relationships, for instance, between pollution levels, biomarker responses and skin and liver diseases in flounder after long-term exposure to PAH-and PCB-contaminated sediments in a mesocosm study were reported by Vethaak et al (1996). Existing long-term data on external visible diseases for flounder from the southern Baltic could provide links to population health.…”
Section: Discussionmentioning
confidence: 86%
“…Still, although some authors already reported differences between laboratory and field assays with fish for the purpose of biomonitoring natural sediments (for instance, Vethaak et al 1996;Hatch and Burton 1999), little research exists comparing the two types of bioassays directly and fewer or none reporting on ''omics''. Regardless of the methodology to determine the effects and responses to toxicity in organisms, such comparison has been determined of relevance since field (in situ) assays are affected by environmental variables other than contamination; laboratory assays, on the other hand, are rarely ecologically realistic and tend to be conservative (Chapman 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Environmental contaminants have the potential to adversely affect aspects of fish life histories (National Research Council, 1996) through effects on developing eggs and larvae, or by immunosuppression (Vethaak et al, 1996). Because fish are (1) an important source of human food, sport, and recreation, (2) frequently exposed to a wide variety of potentially toxic chemicals, (3) capable of accumulating and concentrating xenobiotics, and (4) recognized for some species having an increased incidence of tumors (Zeeman & Brindley, 1981;Grizzle, 1990;Baumann et al, 1996;Hicks, 1996), the need to examine effects of toxic agents on the fish immune system is increasing.…”
Section: Ecological and Human Biota At Riskmentioning
confidence: 99%